Structural, Optical and Electrical Properties of Y2O3 in Borosilicate Glasses - Kalia, Gaurav (My University, 2014)
Glass and glass ceramic samples with composition 55SiO2-30B2O3-xLi2O-(15-x)Y2O3, where x=0, 5, 10, 15 have been prepared by melting and quenching technique. The structural and optical properties of these samples have been studied using various techniques like X-ray diffraction (XRD), Fourier Transform Infra Red spectroscopy (FTIR), UV-visible spectroscopy and impedance spectroscopy. Samples for x = 5 and 10 are purely amorphous in nature as indicated by XRD patterns of these samples. On the other hand, samples for x=0 and 15 show some degree of crystallinity. A broad halo was observed in all the samples, which originates from their amorphous part. Optical band gap of the samples decreases with increasing Y2O3. Urbach energy decreased with increase in Li2O. The effect of temperature on the conductivity of the sample YL-5 was observed. It was found that the conductivity increased with the increase in temperature. The conductivity of YL-5 sample was found to be ~5*10-6 s/cm at 600oC.
MT, SPMS
Keywords: Y2O3; Glass; Optical properties